Pembangunan Kakas Bantu Pembangkitan Kebutuhan Pengguna berdasarkan Model Proses Bisnis - Muhammad Faiz Takwa; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In terms of software requirements analysis, business process modeling has proven to be reliable and effective so that it has been widely used in requirements engineering practices. In other cases, although business process modeling has proven to be reliable in requirements analysis, the reality of a requirements documents or a requirements sentences are presented in the form of natural language. That condition raises new problems for the conversion of business process model into a requirements sentence, it takes a lot of the stages of requirements engineering and the complexity are high, takes more time to understand about the business process model, and raises the problem of inconsistency between the model of the process of business with the requirements sentences from its conversion. As a solution to minimize the incidence of these occur, the research is developed case tool for generating requirements sentences text based on business process model using template filling approach method. This method is used to fill in the requirement sentences templates with information were obtained from business process model. The development of this case tool in this research was implemented using website technology. It accepted input in the form a business process model BPMN type. The output that is obtained is a list of the user requirements with its consistency can be validated based on business process model. Strategy of the unit, integration, validation testing was done to test the case tool which resulting a 100% valid for the test cases and then accuracy testing that prove user requirement consistent with the BPMN and can be used for requirement identification process.